Penerapan Tekhnik Disensitiasi Sistematis Untuk Mengurangi Kecemasan Dalam Menghadapi Ujian Akhir Pada Siswa Kelas IX di MTs Negeri 10 Nganjuk - Umma Ainun Zahro' (STKIP PGRI SUMENEP, 2022)
The problem in this study is the application of systematic desensitization techniques to reduce anxiety in facing school final exams in 9th grade students, in this study the aim is that students can control the anxiety that exists within themselves and can find things that they feel comfortable with. , in this study using qualitative research methods using the type of guidance and counseling action research. The subjects in this study were 5 9th grade students of MTsN 10 Nganjuk, from this research resulted in the application of an effective systematic dissertation technique used to reduce anxiety in facing school final exams in 9th grade students of MTsN 10 Nganjuk.